Penggunaan Serbuk Gergaji Kayu Sebagai Adsorben Pada Limbah Cair Tenun Ikat - Agustina Mimin; Kristina Tresia Leto; Sunarwin Sunarwin (International Forum of Researchers and Lecturers, 2023)
Research has been carried out on the use of wood sawdust as an adsorbent for ikat weaving liquid waste. This research aims to determine the effect of using wood sawdust as an adsorbent on ikat weaving liquid waste. This research was carried out at the IKIP Muhammadiyah Maumere Laboratory and the Maumere Health Service Laboratory. The sample in this study was ikat woven liquid waste which was divided into four treatments, namely Control (K) and the other three were treatments (P1, P2, P3) with the addition of 1,2 and 3 grams of activated charcoal. The method in this research is an experimental method with the research design being True Experimental in the form of Posttest Only Control Group Design. The characteristic tests in this research include a water content test with a value of 0.0833%, and a yield test with a value of 1.9634%. The test parameters used include the degree of acidity (pH), Manganese (Mn) content test and organoleptic test. The research results showed that the pH value before contact with activated charcoal was 9.63 (alkaline pH), and after contact with activated charcoal at a dose of 3.0 grams the pH value became 8.01 (alkaline pH). In testing Mn levels before contact with activated charcoal, the value was 4.60 mg/l and after adding 1.0 grams, 2.0 grams and 3.0 grams of activated charcoal, there was a decrease in Manganese levels respectively, namely from 3 mg/l. , 2.78 mg/l and 1.83 mg/l. Furthermore, for the organoleptic test, there was a change in the color of the ikat woven liquid waste from initially black to clear yellow. Thus, it can be concluded that the addition of activated charcoal from sawdust can have an effect on ikat weaving liquid waste.